Investigation on Boron Alpha Nanotube by Studying Their M-Polynomial and Topological Indices - Deeba Afzal; Farkhanda Afzal; Sabir Hussain; Faryal Chaudhry; Dhana Kumari Thapa (Journal of Mathematics)
Graph theory provides an effective tool such as graph polynomial and topological indices (TIs) to the chemist to analyze the different chemical structures. TIs are the numerical entity deducted from the molecular structure. TI helps to study the relationship between the physicochemical properties and structure of the chemical compound. In this article, we investigate the boron α-nanotube by computing its M-polynomial and then deducing its TI. Results are also shown by plotting the graphs.